Analysis of Microbial Abundances in Biofilms and Water in Hypersaline Environments with Different NaCl Levels - Zamzami, Ilham Misbakudin Al; Kilawati, Yuni; Pramudia, Zulkisam; Susanti, Yogita Ayu Dwi; Kurniawan, Andi (The Journal of Experimental Life Science, 2023)
Biofilm is the dominant habitat for aquatic microbes that can grow in various aquatic conditions, including environments with extreme conditions. One of the extreme conditions found in aquatic ecosystems is a hypersaline environment. As part of aquatic biological resources, microbes can also live in this environment. However, although it is the predominant habitat of microbes, biofilms in hypersaline environments have yet to be widely explored. Understanding biofilms in hypersaline environments, especially salt ponds, will increase knowledge about microbial biofilms. The knowledge can open opportunities for using microbes as aquatic resources, such as aquaculture or environmental biotechnology. This study analyzed microbial abundance in biofilms and water in hypersaline environments. The water is from salt ponds on the South Coast of Malang Regency, Indonesia, with different salinity levels (2%, 25%, and 40%). Microbial abundance was analyzed using the culture method using several culture media (Modified Nutrient Agar, Modified Total Plate Agar, Mannitol Salt Agar, and Casein Medium Agar). The substrate for biofilm growth is HDPE, often used as a bottom coating for salt ponds and shrimp ponds. Moreover, this study also analyzed water quality parameters (pH, dissolved oxygen, turbidity, conductivity, total dissolved solids, temperature) during the biofilms' forming process. The results of this study indicate that the abundance of good microbes that grow in the biofilm or the water around the biofilm is strongly influenced by the type of media used for culturing. The main composition of the most influential media is peptone. The density of microbes in the biofilm is hundreds to thousands of times higher than that in the surrounding water. The results of this study also show that the presence of microbes in both water and biofilm affects the water quality properties in hypersaline environments. Keywords: aquatic ecosystem, biofilm, hypersaline, microbial ecology.